An Event-Study Analysis of Equity Market Reaction to the Major Sport Events and Economic Activity Implications on Host Countries - Maigozhina, Gulmira (2015)
Present study objective is twofold: to examine financial impact of international sport events on daily stock market performance and to conduct an assessment of the induced economic activity and industrial productivity quantified by the average quarterly performance of macroeconomic indices. An event study methodology is applied to examine the main and sector stock markets reaction to the host selection announcement and event beginning dates hypothesized to be positive, as well as the event ending impact expected to be negative. Results indicate positive significant EURO championships announcement effect, positive travel & leisure, construction and telecommunication sectors performance; however negative effect is exerted by Summer Olympics and FIFA World Cup (WCF) announcements. Event beginning positive effect is supported by EURO and the Winter Olympics induced construction sector index performance. Negative event end impact is validated by Summer Olympics, however positive effect is evidenced around EURO, WCC hypothesized to be influenced by the “winner” impact. Stock markets reaction might be conditional upon investors‟ perception of the bidding results likelihood and investor sentiment arguments. Economic landscape reflected by events impelled economic activity and industrial productivity patterns suggest short-lived positive stimulatory impacts marginally higher on the event year relative to the announcement year followed by fading legacy effect. Empirical findings enable to construct trading strategies to gain benefits from stock index performance accounting for the speed of market reaction, variability of returns and factors influencing market returns. Resultant inferences suggest ways to escalate event-induced gains.